THE CONCEPT OF "YOUTH" IN THE UZBEK LANGUAGE AND ITS LINGUISTIC AND CULTURAL FEATURES - Hakimova Muhayyo Karimovna (Zeta Repository, 2023)
This article draws on the analysis of the young concept, which has an Uzbek term of time. The concept also focuses on the processes of historical formation. The article explores Proverbs featuring the young concept of the Uzbek language. Age-related proverbs in Uzbek, French, Japanese and English have been cross-referenced and analyzed.